Standalone microwave photonics doppler shift estimation system - Emami, H. (Institute of Electrical and Electronics Engineers Inc., 2016)
A standalone microwave photonics system for Doppler frequency measurement purposes is conceived and demonstrated practically. The system exhibits a maximum of 1.61% relative error in Doppler frequency estimation at the worst case. Utilization of all optical mixing has enabled RF frequency independent operation. The system is thus capable of operating at any radar carrier frequency up to 40 GHz. This makes it a perfect candidate for various types of photonic-based radars and frequency agility systems.